The Role of Indonesian’s Diaspora in Malaysia for Peace - Surwandono Surwandono; Ariyanto Nugroho (Journal of Islamic World and Politics, 2022)
This article the potential of the Indonesian diaspora as an agent of peace in Malaysia. The Indonesian diaspora in Malaysia, for both Indonesia and Malaysia, is the largest diaspora in Malaysia. Sometimes, the large number of the diaspora in a country can cause problems of prejudice, and concerns that lead to security problems. But on the other hand, the size of the diaspora can also have the opportunity to be an integrative factor that can give birth to peace. Data on the dynamics of the Indonesian diaspora in Malaysia were obtained from primary sources, as well as focus group discussions, interviews, and official data from the government.This article finds that a large number of Indonesian diaspora and the establishment of mutualistic relationships at the government and government levels, as well as at the community and community level over a long period of time, contributes to the high role of the Indonesian diaspora in building social cohesion and peace in Malaysia.